Finanças Comportamentais: traços de otimismo e excesso de confiança no processo de tomada de decisão de um gestor. - Silva, Geisa Karla Alves da (Universidade Federal Rural do Semi-Árido, 2018)
With the intense competitiveness among companies, many managers need to invest so that they can stay in the market, that is, the investment is very important for the company's differential in relation to its competitors. For the investment to bring the expected return, decisions must be made based on reliable information and the manager makes the best decisions, but studies of behavioral finance have shown that investors do not act with total rationality and that at various times deviations from rationality are present in people's decisions. This paper aims to understand, within the behavioral finance logic, the determining factors in the decision of an expansion investment project in the retail trade in a city in the interior of Ceará, identifying if there were traces of over-confidence biases and optimism. A descriptive qualitative research was conducted in the form of a case study, and the tool used was an interview with the manager of a supermarket in the interior of Ceará. It was identified that the individual and market factors as well as the skewness traits overconfidence and optimism were decisive for the manager's decision making. It is concluded that behavioral finances play an important role in understanding the reasons that lead managers to choose certain alternatives and what is behind those decisions, as observed in the decisions of the manager studied in this paper, investors may have their decisions influenced by factors that divert them from rationality.
Monografia
Keywords: Investimento; Finanças comportamentais; Decisões; Enviesamentos; Investment; Behavioral Finances; Decisions; Skew; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO